Eco-Friendly Building Material Innovation: Geopolymer Bricks from Repurposed Plastic Waste - Haq Md. Zia ul; Sood Hemant; Kumar Rajesh; Sharma Vishal; Kumar Anuj; Srinivas T.; Gulati Monica; Bindu K. Hima; Kumar Kaushal (E3S Web of Conferences, 2023)
This study compares the ecological footprints of geopolymer and red clay brick prisms, two common building materials for long-lasting masonry structures. The study’s goal is to shed light on the environmental performance of different brick kinds by a thorough review of sustainability indices such as embodied energy, CO2 emissions, water use, and trash creation. The results suggest that geopolymer bricks have better environmental features than red clay bricks, such as lower embodied energy, decreased CO2 emissions, lower water consumption, and less waste creation. These findings underline the promise of geopolymer bricks as an eco-friendlier masonry alternative that may improve green building performance. The report, however, stresses the need to think about more than only environmental damage. The sustainability and feasibility of utilising geopolymer and red clay bricks depend heavily on factors including durability, thermal performance, and cost-effectiveness. In order to make educated selections about brick selection, it is important to evaluate these variables. The results of this study provide the groundwork for more research on sustainable masonry materials and contribute to the development of environmentally aware building practises. Architectural and engineering professionals may encourage environmentally responsible building practises and help create a more sustainable and resilient built environment by taking this study’s findings into account.